Surgeon General position: Round Table Acute arterial accidents of the members; introduction and coordination Raúl Ugarte Artola - Bermúdez, Oscar (Cirugía del Uruguay, 1973)
On behalf of the Society of Angiology and on my own behalf, I extend to the members of the Executive Committee, our gratitude for your invitation to participate in this Congress. The Society of Angiology, is present for the first time and hopes to contribute effectively to the exchange of knowledge, which Uruguayan surgeons carry out annually for the purpose of mutual scientific enrichment.